Lake Champlain (Plattsburgh) Paper - The Late Discovery of Large Quantities of Magnetic and Non-Magnetic Pyrites in the Croton Magnetic Iron Mines - W. H. Hoffman (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1893)
During the autumn of 1891, several heavy blasts (each throwing down some 3000 tons of ore) were made on what is known as the Theall side of these mines. Immediately after one of these blasts, the writer found that at least one-third of the ore was largely impregnated with pyrites, and besides this, fully 15 per cent. of the entire blast was composed of irregular lumps of magnetic pyrites. This was a revelation wholly unexpected, as previous examinations by many experts had failed to disclose any such quantity of sulphury ore. Over the center of the Theall tunnel there suddenly appeared a perfect keystone, as it were, of pyrites, 3 feet wide at the arch of the tunnel, 13 feet ride at the top, and 20 feet high. This keystone pinched out in February, 1892; but in that month large blocks of pyrites were more plentiful on or near the western wall, and these deposits extended the entire height of the workings, some 43 feet. The second blast in November, in the face and over, and on each side of the tunnel, was far more surprising. The whole cross-section it exposed was thickly interspersed with layers of magnetic pyrites, ranging in thickness from 10 to 24 inches, and quite irregular in form, while all of the ore carried much more than the usual amount of sulphur in the non-magnetic pyrite. One hundred and fifty-five tons from a portion of this breast (western side), showed the following composition upon sampling and analysis: Per cent. Metallic iron,...45.080 Phosphorus,..........304 Sulphur,...........23.510 And the balance of the blast showed: Per cent. Metallic iron,.....• 33.210 Phosphorus,...........349 Sulphur,.......... 6.680 vol. xxI.-33